Determination of the active volumes of solid‐state photon‐beam dosimetry detectors using the PTB proton microbeam. Issue 7 (1st June 2018) - Poppinga, Daniela; Delfs, Bjoern; Meyners, Jutta; Langner, Frank; Giesen, Ulrich; Harder, Dietrich; Poppe, Bjoern; Looe, Hui K.
Abstract : Purpose: This study aims at the experimental determination of the diameters and thicknesses of the active volumes of solid‐state photon‐beam detectors for clinical dosimetry. The 10 MeV proton microbeam of the PTB (Physikalisch‐Technische Bundesanstalt, Braunschweig) was used to examine two synthetic diamond detectors, type microDiamond (PTW Freiburg, Germany), and the silicon detectors Diode E (PTW Freiburg, Germany) and Razor Diode (Iba Dosimetry, Germany). The knowledge of the dimensions of their active volumes is essential for their Monte Carlo simulation and their applications in small‐field photon‐beam dosimetry. Methods: The diameter of the active detector volume was determined from the detector current profile recorded by radially scanning the proton microbeam across the detector. The thickness of the active detector volume was determined from the detector's electrical current, the number of protons incident per time interval and their mean stopping power in the active volume. The mean energy of the protons entering this volume was assessed by comparing the measured and the simulated influence of the thickness of a stack of aluminum preabsorber foils on the detector signal. Results: For all detector types investigated, the diameters measured for the active volume closely agreed with the manufacturers' data. For the silicon Diode E detector, the thickness determined for the active volume agreed with the manufacturer's data, while for the microDiamond detectors and the Razor Diode, the thicknesses measured slightly exceeded those stated by the manufacturers. Discussion: The PTB microbeam facility was used to analyze the diameters and thicknesses of the active volumes of photon dosimetry detectors for the first time. A new method of determining the thickness values with an uncertainty of ±10% was applied. The results appear useful for further consolidating detailed geometrical knowledge of the solid‐state detectors investigated, which are used in clinical small‐field photon‐beam dosimetry.